اختيار الشرائح بالاعتماد على مراكز القرار في طريقة التصنيع السريع للنموذج - سلوم, تمام (Latakia University Journal -Engineering Sciences Series, 2018)
تعرض هذه المقالة طريقة التصنيع السريع للنموذج من أجل تصميم وتصنيع القطع الميكانيكية المعقدة المستخدمة في الميكانزمات النموذجية الوظيفية. تعتمد هذه الطريقة على تقسيم القطع المعقدة إلى عدة قطع بسيطة قابلة للتصنيع على آلات التشغيل المبرمجة ذات السرع العالية انطلاقا من قطع خام ذات سماكات مقبولة تقريبا 40 مم من مواد مقاومة و خاصة الألمنيوم. سنركز في هذه المقالة على كيفية اختيار مستويات التقطيع الى شرائح من اجل تجنب المرور بالمناطق الوظيفية وذلك بالاعتماد على مراكز القرار وقمنا بعرض الخوارزميات المقترحة لتحديد هذه المستويات حيث تعتبر هذه المرحلة هي اهم المراحل في طريقة التصنيع السريع للنموذجURP . This paper presents the manufacturing process for complex parts in the aim of building functional prototype mechanisms. Functional prototypes are used during testing in order to validate new product design. Their layouts are very similar to the final product, wherein lies the interest of testing many modifications. The mechanism must respect the functional geometrical requirements and be capable of withstanding forces or, for example, ensuring a tight seal. The principle being proposed consists of decomposing the complex parts into several simple ones that can then be manufactured on a five-axis, high-speed milling machine from thick (approximately 40 mm) sheets made of resistant materials, notably aluminum. The problem is the choice of slicing in order to avoid cutting functional areas; This paper also presents a detailed application using CATIA